2018
DOI: 10.1002/bdd.2137
|View full text |Cite
|
Sign up to set email alerts
|

Use of fluorescein isothiocyanate isomer I to study the mechanism of intestinal absorption of fucoidan sulfate in vivo and in vitro

Abstract: A new method to label fucoidan sulfate was established with tyramine and fluorescein isothiocyanate isomer I (FITC). Fluorescence spectrophotometry and high performance liquid chromatography verified the successful labelling of fucoidan by FITC. The results of the single-pass intestinal perfusion indicated that the jejunum and ileum are the main absorption sites, and there was carrier saturation. In addition, fucoidan sulfate at 1 mg/ml had no inhibitory effect on Caco-2 cell proliferation. Studies on the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
(18 reference statements)
0
12
1
Order By: Relevance
“…These results indicated that F-PM and F-PG entered Caco-2 cells via the macropinocytosis pathway and the clathrin and caveolae (or lipid raft)-mediated endocytosis pathway. This result was different from the transport mechanism of fucoidan that we reported previously, as the transport of fucoidan in the Caco-2 cell monolayers was almost completely blocked by chlorpromazine [11]. This confirmed that the absorption mechanism may be different for biomacromolecules with different structures.…”
Section: Effects Of Transport Inhibitors On the Transport Of F-pm Andcontrasting
confidence: 93%
See 1 more Smart Citation
“…These results indicated that F-PM and F-PG entered Caco-2 cells via the macropinocytosis pathway and the clathrin and caveolae (or lipid raft)-mediated endocytosis pathway. This result was different from the transport mechanism of fucoidan that we reported previously, as the transport of fucoidan in the Caco-2 cell monolayers was almost completely blocked by chlorpromazine [11]. This confirmed that the absorption mechanism may be different for biomacromolecules with different structures.…”
Section: Effects Of Transport Inhibitors On the Transport Of F-pm Andcontrasting
confidence: 93%
“…The fluorescently labeled products were verified by agarose gel electrophoresis and fluorescence spectrophotometry [11]. For agarose gel electrophoresis, gelatin was prepared using a sodium barbital solution containing 0.5% (m/v) agarose.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that fucoidan can exert a wide range of pharmacological effects, including anti-inflammatory [6], antitumor [7], antioxidative [8], antiviral, and antithrombotic activity, as well as improving immune response and lipid metabolism [5,[9][10][11][12]. However, only a small number of studies addressed the mechanism of absorption and tissue distribution of this compound in vivo given their high molecular size [13][14][15][16]. Therefore, a detailed knowledge of its absorption mechanism is important for its biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our analysis identified the process of endocytosis as a potential target for fucoidan. While cellular uptake of fucoidan might rely on clathrin-dependent endocytosis [22], previous studies reported that fucoidan can inhibit endocytosis in HeLa cells [23]. Fucoidan suppressed Ca 2+ -dependent endocytosis, potentially by inhibition of agonist-induced Ca 2+ responses [23].…”
Section: Discussionmentioning
confidence: 98%